Assessing The Viability of Strategic Expansion: A Case Study on Opening A New Mcg Coffee Branch - Nadhila Dzikrina Yusuf; Sylviana Maya Damayanti (Journal of Social Research, 2025)
This study evaluates the financial feasibility of expanding MCG Coffee by opening a new branch in Tebet, Jakarta. Using a mixed-methods approach, the research combines qualitative strategic analysis—including SWOT and Porter’s Five Forces—with quantitative financial modeling tools such as Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP). Data collection involved both primary sources (surveys and interviews) and secondary sources (financial records and industry benchmarks). The findings reveal that the proposed expansion is financially viable, with a positive NPV of Rp 145,349,219, an IRR of 25%, and a payback period of 4 years and 7 months. Sensitivity analysis indicates that revenue fluctuations have the highest impact on investment outcomes. The study also presents a detailed implementation roadmap to guide the setup of the new branch, emphasizing community engagement and diversified revenue streams. These results provide actionable insights for SME coffee shop owners seeking sustainable growth through strategic expansion.